Dissemination of the role of local government in providing legal Protection to MSMEs in the Tourism Sector Lon Malang Beach, Sokobanah District, Sampang Madura Regency - Muhammad Hanif Aliyyuddin; Azzahra Dita Pratiwi; Lucky Dafira Nugroho; Santi Rima Melati (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2022)
Regional Government is one of the tools in the governance system. According to Law Number 23 of 2014 concerning Regional Government (hereinafter referred to as the Regional Government Law) the regional head is an element of Regional Government administration who leads the implementation of government affairs which fall under the authority of the autonomous region. Meanwhile, Regional Government is the administration of government affairs by the regional government and the Regional People's Legislative Assembly according to the principle of autonomy and co-administration with the principle of broadest autonomy in the system and principles of the State in the 1945 Constitution of the Republic of Indonesia. The role of regional government in regional development planning is government that has very strategic authority and a strategic position, this is related to its function as a "public service" to improve welfare, prosperity, security, justice and peace for the community. In particular, local governments play an important role in providing protection for existing MSMEs. Micro, Small and Medium Enterprises (MSMEs) are productive business units that stand alone, which are carried out by individuals or business entities in all economic sectors. In this case the MSMEs that must be given protection by the Regional Government are mainly MSMEs in the tourism sector which are located on Lon Malang Beach, Sokobanah District, Sampang Madura Regency. Because in this case it can provide increased welfare for communities around the coast and can increase regional income.